2022
DOI: 10.3897/pharmacia.69.e81280
|View full text |Cite
|
Sign up to set email alerts
|

Oral acute toxicity study extract ethanol of balakka fruit (Phyllanthus emblica)

Abstract: Phyllanthus emblica (PE) is a plant widely found in Indonesia, especially in Sumatra island, and in India. This study followed the OECD No. 420. The groups were divided based on gender, male and female rats. Male rats were divided into 6 groups, which were male/female control, male/female 2000 mg/kgBW, and male/female 5000 mg/kgBW. This study revealed that the ethanol extract of Phyllanthus emblica (EEPE) doses of 2000 mg/kgBW and 5000 mg/kgBW did not cause histological changes in the heart, liver, testes, ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Chronic toxicity studies by inducting P. emblica oral doses of 300, 600 and 1,200 mg/kg for 270 days resulted in no evident changes in treated animals pathologically. Previous studies reported the absence of toxicity of P. emblica fruit extract at doses of 200, 400, 300, and 500 mg/kg (Golechha et al, 2014;Middha et al, 2015;Anto et al, 2022). Furthermore, Uddin et al (2016) reported that the ethanolic extract of Phyllanthus emblica is safe with a dose up to 2000 mg/kg b.w.…”
Section: Safety and Toxicitymentioning
confidence: 98%
“…Chronic toxicity studies by inducting P. emblica oral doses of 300, 600 and 1,200 mg/kg for 270 days resulted in no evident changes in treated animals pathologically. Previous studies reported the absence of toxicity of P. emblica fruit extract at doses of 200, 400, 300, and 500 mg/kg (Golechha et al, 2014;Middha et al, 2015;Anto et al, 2022). Furthermore, Uddin et al (2016) reported that the ethanolic extract of Phyllanthus emblica is safe with a dose up to 2000 mg/kg b.w.…”
Section: Safety and Toxicitymentioning
confidence: 98%
“…Of these, 15 herbs, namely A. augusta (28,81), A. bunius (82,83), A. elata (84)(85)(86), C. obtusifolia (87)(88)(89), C. aurantium (90)(91)(92)(93), C. longa (94)(95)(96), C. sativus (97-99), C. terminans (100-102), G. tenuifolia (80,103), H. sabdariffa (104,105), P. notoginseng (109), P. indica (114), R. of f icinalis (115,116), R. ideaus (117,118) a nd T. foenum-graecum (119-121) exhibited a mode of action involving lipid metabolism, insulin resistance and/or inflammatory markers. The remaining five herbs, namely M. oleifera (46,106), M. latifolia (107,108), P. emblica (110,111), P. kurroa (53,112) and P. anisum (113) warrant further investigations to establish their cross-link mode of action. These herbs exhibited no signs of toxicity.…”
Section: Oxidative Stress a Total Of Eight Herbal Plants Namelymentioning
confidence: 99%
“…The percentage yield of EAFA extract is 6.02% in 100 g of amla fruit dried powder. Based on previously reported acute toxicity studies on amla extracts, the safest dose was up to 5000 mg/kg BW [22]. Based on the prior investigation, the dose of the ethyl acetate fraction of amla extract (EAFA) at 100 mg/kg BW was chosen for the treatment group in the current study [23].…”
Section: Preparation Of Dried Fruit Extract Of Phyllanthusemblicamentioning
confidence: 99%